Effects of exposure to slate dust in North Wales. Issue 2 (May 1980) - Glover, J R; Bevan, C; Cotes, J E; Elwood, P C; Hodges, N G; Kell, R L; Lowe, C R; McDermott, M; Oldham, P D
Abstract : In a study of slate workers in four areas in North Wales 725 workers and ex-workers who had been exposed to slate and to no other dust were seen, together with 530 men from the same area who had never been exposed to any dust. Evidence of pneumoconiosis was found in one-third of the slate workers, and 10% had degrees of pneumoconiosis that would attract compensation (category 2 or higher). The prevalence of respiratory symptoms was high, and there was evidence of an effect of both simple and complicated pneumoconiosis on lung function additional to that of age. There was a high prevalence (40-50%) of radiological lesions suggestive of healed tuberculosis in men aged over 55. Either pneumoconiosis or old tubercular lesions (or both together) could account for the current symptomatology and disability of the men.